2018
DOI: 10.1111/eci.12989
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils as myeloid‐derived suppressor cells

Abstract: Neutrophils form the first line of defence against invading pathogens, such as bacteria and fungi, as part of the innate immune response. Recently, neutrophils have also been discovered as repressors of adaptive immune responses. Under certain conditions, such as cancer and severe injury, an expansion of immature and mature neutrophils has been observed to induce suppression of T-cell proliferation. These suppressing cells are known as so-called myeloid-derived suppressor cells (MDSCs), a heterogeneous populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 59 publications
4
54
0
Order By: Relevance
“…More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy . NLR and ANC have been reported to correlate with the number of circulating MDSCs and tumor‐associated neutrophils, which suppress the function of antitumor T cells . Circulating MDSC levels were inversely associated with response rate and survival after treatment with nivolumab in cancer patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy . NLR and ANC have been reported to correlate with the number of circulating MDSCs and tumor‐associated neutrophils, which suppress the function of antitumor T cells . Circulating MDSC levels were inversely associated with response rate and survival after treatment with nivolumab in cancer patients .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the neutrophil‐to‐lymphocyte ratio (NLR) and the absolute neutrophil count (ANC) in the blood can predict the efficacy of PD‐1 inhibitors in patients with NSCLC . NLR and ANC have also been reported to reflect the number of circulating myeloid‐derived suppressor cells (MDSCs) and tumor‐associated neutrophils, which inhibit the function of antitumor T cells . The immunosuppressive status in the tumor microenvironment could be monitored using the dynamics of NLR and ANC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of the innate and adaptive immune systems by neutrophils has been reviewed extensively . Neutrophil granule contents participate in many regulatory activities, including those involving T cells, dendritic cells, B cells, and monocytes .…”
Section: Role Of Exocytosis In Neutrophil Functionmentioning
confidence: 99%
“…The regulation of the innate and adaptive immune systems by neutrophils has been reviewed extensively. [70][71][72][73][74][75][76][77][78][79] Neutrophil granule contents participate in many regulatory activities, including those involving T cells, dendritic cells, B cells, and monocytes. 70,72,73,80 The interaction between neutrophils and monocytes is particularly relevant to antimicrobial activity and inflammatory diseases.…”
Section: Role Of Exocytosis In Neutrophil Functionmentioning
confidence: 99%